Evading the host response: Staphylococcus “hiding” in cortical bone canalicular system causes increased bacterial burden - Zoller, Stephen D. (Bone Res, 2020)
Extremity reconstruction surgery is increasingly performed rather than amputation for patients with large-segment pathologic bone loss. Debate persists as to the optimal void filler for this “limb salvage” surgery, whether metal or allograft bone. Clinicians focus on optimizing important functional gains for patients, and the risk of devastating implant infection has been thought to be similar regardless of implant material. Recent insights into infection pathophysiology are challenging this equipoise, however, with both basic science data suggesting a novel mechanism of infection of Staphylococcus aureus (the most common infecting agent) into the host lacunar–canaliculi network, and also clinical data revealing a higher rate of infection of allograft over metal. The current translational study was therefore developed to bridge the gap between these insights in a longitudinal murine model of infection of allograft bone and metal. Real-time Staphylococci infection characteristics were quantified in cortical bone vs metal, and both microarchitecture of host implant and presence of host immune response were assessed. An orders-of-magnitude higher bacterial burden was established in cortical allograft bone over both metal and cancellous bone. The establishment of immune-evading microabscesses was confirmed in both cortical allograft haversian canal and the submicron canaliculi network in an additional model of mouse femur bone infection. These study results reveal a mechanism by which Staphylococci evasion of host immunity is possible, contributing to elevated risks of infection in cortical bone. The presence of this local infection reservoir imparts massive clinical implications that may alter the current paradigm of osteomyelitis and bulk allograft infection treatment.